Analysis of Physical Education Students' Learning Motivation in Basic Research Course - Yahya Eko Nopiyanto; Bayu Insanistyo; Ibrahim; Ipa Sari Kardi; Kurdi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
Learning motivation is an important factor that drives students to continue learning optimally. Therefore, lecturers in education units need to conduct studies on student learning motivation in their classes so that they can help optimize student learning motivation. The purpose of this study was to determine the level of motivation of Physical Education students in participating in basic research courses. This research is qualitative descriptive. The subjects involved in this study were 29 students. Data collection instruments used observation, questionnaires, and interviews. The research data that has been collected is analyzed using data triangulation assisted by percentage analysis using 5 categories, and qualitative descriptive so that the research results are easy to understand by readers. Based on the results of the analysis, it is known that the motivation of Physical Education students in participating in basic research lectures is in the very high category. From the results of this study, it is recommended for students maintain their learning motivation and increase learning motivation on indicators of being tenacious in facing difficulties